ECONOMIC MOVEMENTS WITHIN SUFISM IN JAVA: A Case Study on Qadiriyah and Naqsyabandiyah Sufi Orders (State Islamic University (UIN) of Sunan Ampel Surabaya, 2015)
This study aims at elaborating the relationship between Sufism and economics. It shows that Sufism does not totally abstain from getting in touch with worldly issues. Furthermore, it attempts to develop the thesis of Webber – that religion motivates its adherents to improve work ethics and economic development– into Sufism. The method bases on grounded research by qualitative approach. It employs constant analysis. This research involved three Pesantrens; a) Pesantren Suryalaya West Java; b) Pesantren Darul Ulum Jombang East Java; and, c) Pesantren Futuhiyah Mranggen Demak, Central Java, as representatives of the economic movements of Qadiriyah wa Naqsyabandiyah Sufi orders (TQN) in Java. The findings confirm that the economicmovement in TQN is dynamic for it depends on teachers’ views. The strongest economic Movement is TQN of Pesantren Suryalaya, followed by TQN of Pesantren Darul Ulum Jombang. The strength of economic activity at TQN of Futuhiyah Mranggen is not that obvious.